POLA KOMUNIKASI KELOMPOK PURNA PASUKAN PENGIBAR BENDERA PUSAKA (PASKIBRAKA) INDONESIA KOTA PEKANBARU DALAM PEMBINAAN KARAKTER PATRIOTIK CALON PASKIBRAKA KOTA PEKANBARU TAHUN 2014 - Hanum, Nova Puspita; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
A group is an interaction and communication from people who have plan to achieve a common goal. One of them is a communication group of Purna Paskibraka Indonesia (PPI) in Pekanbaru. They do interaction and communication to achieveing success in coaching Paskibraka candidate of Pekanbaru. The purpose of this research is to find out the function of communication group of PPI especially in coaching patriot characteristic, as well as how to approach the pattern of communication group Purna Paskibraka Indonesia in Pekanbaru 2014.This research is used to descriptive qualitative research methods, with the selection of informants using purposive sampling technique, which isselected based on the specific characteristics, the number of informants are 7 people. The data collection techniques that are grouped through participant observation, in-depth interviews, and documentation.The result of this research concluded that firstly, the function communication group used in Paskibraka is coaching is a function of social relations, education, persuasion and problem solving. Secondly, the approach of communication group of PPI in Pekanbaru is performed in both directions and interactions which occured with anyone among the organizers,trainers andcoaches ,by using a communication networks of all pattern shapping channel. Communication patterns to form patriot characteristic of Paskibraka candidate in Pekanbaru 2014 is done through a process of habituation, exemplary, and the enhancing of values.Keywords : Communication Patterns, Communication Group, Purna Paskibraka Indonesia, Character Patriotic, Paskibraka of Pekanbaru